A review of pediatric middle ear tumors and analysis of the demographics, management, and survival of pediatric rhabdomyosarcomas of the middle ear. (September 2018) - Janz, Tyler A.; Camilon, P. Ryan; Cheung, Anthony Y.; Nguyen, Shaun A.; White, David R.; Weber, Peter C.
Abstract: Objective: To examine the types of pediatric middle ear tumors and review the demographics, management, and survival of pediatric patients with rhabdomyosarcoma (RMS) of the middle ear. Methods: Pediatric patients in the Surveillance, Epidemiology, and End Results (SEER) database were included from 1973 to 2014 based on a diagnosis of middle ear tumors using the ICD O-3 code: C30.1: Middle ear primary site. Patients were included from ages 0–18 years. Results: Forty pediatric middle ear tumor cases were identified. Twenty patients were female (50%). Twenty-seven (67.5%) cases were rhabdomyosarcomas (RMS). Pediatric RMS patients tended to be diagnosed in early childhood (mean age 5.30 years, standard deviation 2.9, range 1.00–13.00, 59.3% of patients were ages 5 or below). Most pediatric RMS patients received chemotherapy and radiation therapy as part of the treatment regimen (88.8%). Finally, the 5-year overall and disease-specific survival rates were 59% and 63% respectively. Conclusions: Pediatric middle ear tumors are rare. Females and male pediatric patients are both at risk for middle ear tumors. RMS is the most common malignant middle ear tumor affecting pediatric patients. Despite the use of multimodality therapies, survival rates for pediatric patients with RMS of the middle ear are low. Physicians may consider including middle ear tumors on the differential diagnosis for pediatric patients with symptoms presenting similarly to non-resolving otitis media.